Improvement in safety and health study at a copper wire manufacturing company [electronic resource] - Mohd. Haleem Shah Ismail, 1986- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010